Analisis Pengaruh Motivasi dan Literasi Keuangan terhadap Minat Investasi Serta Implikasinya pada Pengambilan Keputusan Investasi Generasi Milenial dan Generasi Z di Kota Bandung - Nuralfiah, Cahyanti; Fitriana; Kadarisman, Sumeidi (Jurnal Manajemen dan Organisasi, 2025)
Indonesia's economic transformation in the endemic adaptation era creates complex investment dynamics for millennials and Generation Z. This study aims to analyze the influence of motivation and financial literacy on investment interest and its impact on investment decisions of the younger generation in Bandung City. The research method uses a quantitative approach with a descriptive-verification design on 100 respondents through purposive sampling technique. The research instrument is a Likert scale structured questionnaire that has been validated and tested for reliability. Data analysis uses path analysis to identify causal relationships between variables. The results show that financial literacy has a positive and significant influence on investment interest with greater dominance compared to motivation. Both variables simultaneously have a significant effect on investment interest. Investment interest is proven to be a significant mediator of investment decisions. Indirect effect analysis reveals that financial literacy through investment interest contributes more to investment decisions than motivation. Empirical findings confirm the crucial role of financial literacy in shaping the investment behavior of the digital generation. Cognitive components are proven to be more dominant than motivational aspects in driving investment decisions. The research implications emphasize the importance of strengthening financial education as a priority strategy in increasing the participation of the younger generation in the Indonesian capital market.